Effectiveness of vitamin D3 in facilitating the therapeutic progression of healing diabetic foot ulcers - Nouri, Fatemeh; Aghaei, Sara; Özbolat, Gülüzar; Döğüş, Yusuf; Mirhamidi, Mahdi; Reza Rahimi Barghani, Mahmoud; Daemi, Amin (Chulalongkorn Medical Journal, 2025)
Background: Diabetes and its complications afflict a large portion of the population worldwide, and it is estimated that its prevalence in all age groups will increase from 2.8% in 2000 to 4.4% in 2030. Moreover, it is well known that vitamin D may cause rapid wound healing and exert anti-inflammatory effects. Objective: This study aimed to investigate the efficacy of vitamin D3 on the healing of chronic diabetic foot ulcers to improve the quality of life of patients with diabetes. The present research is conducted as a randomized controlled trial. Methods: Forty patients were randomly divided into an experimental group (vitamin D supplementation) and a control group (placebo) using a sampling method based on the inclusion criteria. The patients were evaluated for ulcer debridement every two weeks (0 (T0), 2 (T1), 4 (T2), 6 (T3), 8 (T4), 10 (T5), and 12 (T6)) after the intervention. The collected data were analyzed using SPSS-23 software. Results: The experimental group exhibited significantly decreased ulcer length (−1.6 ± 0.8 cmvs.−0.5 ± 1.4 cm, P = 0.005), ulcer width (−1.7 ± 1.2 cmvs.−0.9 ± 1.2 cm,P = 0.025), and ulcer depth (−0.6 ± 0.5 cmvs.−0.3 ± 0.4 cm, P = 0.025) after 12 weeks of intervention compared to those of the control group. These results reveal that vitamin D had a significant relationship with all stages of the wound-healing process (P < 0.01). Conclusions: In patients with chronic diabetic foot ulcers, the use of vitamin D supplementation can improve wound healing. Moreover, vitamin D had a significant relationship with all stages of the wound-healing process except re-epithelialization and angiogenesis.